PACU JALUR: DARI PACU PERAHU LOKAL HINGGA SALAH SATU PARIWISATA TERPOPULER DI INDONESIA - Amanan Amanan; Sabrina Sabrina (Ensiklopedia of Journal, 2025)
This article examines the history and development of Pacu Jalur, a traditional longboat racing event on the Kuantan River in Kuantan Singingi Regency. Originally, these boats served as means of transportation, but over time, they evolved into a competitive event featured in a national cultural festival. The study also highlights the enthusiasm of the local community involved in Pacu Jalur, as the event is not only compelling as a spectacle but has also become an integral part of daily life. The research employs historical methods through the stages of heuristics, criticism, interpretation, and historiography, utilizing various sources including newspapers, books, academic articles, and interviews with local residents. The findings indicate that Pacu Jalur developed from a simple local tradition, gradually attracting governmental attention in the 1980s, transforming into a widely celebrated people’s festival, becoming part of Riau’s tourism program, and eventually being recognized as an intangible cultural heritage and incorporated into the Karisma Event Nusantara (KEN) by the Ministry of Tourism and Creative Economy. Moreover, the enduring popularity of Pacu Jalur is inseparable from the collective enthusiasm of the community, which has been crucial to sustaining the tradition from past to present. Thus, Pacu Jalur serves not only as a cultural symbol but also as a space of communal togetherness and a marker of collective identity for the people of Kuantan Singingi.Keywords: Pacu Jalur, Taluk Kuantan, local history.